2022
DOI: 10.3390/fermentation8070340
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Bagasse-Based Ethanol Production and Utilization of Its Vinasse for Xylitol Production as an Approach in Integrated Biorefinery

Abstract: Biorefinery of sugarcane bagasse into ethanol and xylitol was investigated in this study. Ethanol fermentation of sugarcane bagasse hydrolysate was carried out by Saccharomyces cerevisiae. After ethanol distillation, the vinasse containing xylose was used to produce xylitol through fermentation by Candida guilliermondii TISTR 5068. During the ethanol fermentation, it was not necessary to supplement a nitrogen source to the hydrolysate. Approximately 50 g/L of bioethanol was produced after 36 h of fermentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Both wild type and engineered K. marxianus strains have been used for xylitol production from lignocellulosic biomass and the main challenges to improve xylitol production in K. marxianus are related to xylose uptake and NADP supply [10]. However, it has also been reported that xylitol consumption or reassimilation by xylitol-producing yeasts also tends to reduce xylitol yields [74], so another limiting factor in the final xylitol yield and productivity may also be the reassimilation of the produced xylitol by K. marxianus. Finally, regarding carboxylic acids assimilation, as expected, all the isolates were clearly positive for DL-lactate except Kmx24 which showed a weak response.…”
Section: Discussionmentioning
confidence: 99%
“…Both wild type and engineered K. marxianus strains have been used for xylitol production from lignocellulosic biomass and the main challenges to improve xylitol production in K. marxianus are related to xylose uptake and NADP supply [10]. However, it has also been reported that xylitol consumption or reassimilation by xylitol-producing yeasts also tends to reduce xylitol yields [74], so another limiting factor in the final xylitol yield and productivity may also be the reassimilation of the produced xylitol by K. marxianus. Finally, regarding carboxylic acids assimilation, as expected, all the isolates were clearly positive for DL-lactate except Kmx24 which showed a weak response.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pentoses were not really considered as substrates for ethanol production. However, for a complete use of the fermentable sugars present in SH hydrolysates, the pentoses derived from hemicellulose also should be metabolized to increase the ethanol concentration, or to produce other value-added products, such as xylitol [51,52]. Because the pentose-metabolization machinery is absent or silent in Saccharomyces, it is necessary to use yeast strains naturally capable of consuming pentoses, such as Spathaspora passalidarum or Scheffersomyces stipitis [53], or genetically modified strains, such as S. cerevisiae TMB3400 [54].The recombinant strains S. cerevisiae YRH396 and YRH400 were able to ferment soybean and oat hull hydrolysates obtained by pretreatment with dilute sulfuric acid [10].…”
Section: Separate Saccharification and Fermentationmentioning
confidence: 99%
“…This may indicate that, in this new condition of more efficient aeration, the microorganism may have had a metabolic deviation to produce other products. Aeration may have led the yeast K. marxianus CCA510 to produce 2-phenyl-ethanol (2-FE), a higher aromatic alcohol widely used in the perfume industry, [54] that was detected [50] Candida guilliermondii Sugarcane bagasse hydrolysate 13.8 10.2 0.74 0.17 Hor et al [51] Candida boidinii Olive stones hydrolysate 60.0 34.2 0.57 0.14 Romero-García et al [22] Candida sojae Mustard iomass hydrolysate 50.0 12.4 0.62 0.17 Pant et al [45] Candida tropicalis Typha latifolia hydrolysate 13.3 6.2 0.65 0.14 Goli and Hameeda [52] Debaryomyces hansenii Synthetic medium 5.0 1.82 0.02 0.03 Kasbawati et al [29] Kluyveromyces marxianus…”
Section: Xylitol Production From Cabhmentioning
confidence: 99%